Core educational benefits of project-based learning: A systematic literature review - Moh. Abdul Qohar; Muhammad Hasan Asnawi; Nawal Ika Susanti; Siti Nur Azizah; Ahmad Sofiyullah (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2026)
Project-Based Learning (PBL) has gained increasing attention as an instructional approach that promotes active, contextual, and learner-centered education. Although previous studies have reported diverse educational outcomes of PjBL, existing evidence remains fragmented across specific outcomes, limiting understanding of how these benefits are interconnected. This study aims to systematically review and synthesize the core educational benefits of PjBL based on recent empirical evidence. A systematic review and thematic synthesis were conducted following the PRISMA 2020 framework. The literature search was performed in the Scopus database for publications from January 2020 to August 2026. Studies were included if they reported original empirical findings on PjBL implementation in formal educational settings. Of 16 identified records, four empirical studies met the eligibility criteria and were included in the thematic synthesis. Five interconnected dimensions of PjBL benefits were identified: cognitive competence and critical thinking; creativity and innovation; learning engagement, autonomy, and self-regulation; collaboration and communication; and conceptual mastery, contextual application, and academic performance. Evidence was relatively more consistent for cognitive development, student engagement, collaboration, conceptual understanding, and academic outcomes, whereas creativity and communication showed more context-dependent patterns. These variations suggest that specific outcomes may depend on project design, student autonomy, instructional scaffolding, implementation duration, and assessment conditions. This review offers a process-oriented understanding of PjBL by conceptualizing its benefits as interconnected outcomes that emerge through engagement, inquiry, self-regulation, collaboration, and knowledge application. However, given the limited number and contextual diversity of included studies, the findings should be interpreted as recurring patterns within the eligible evidence rather than universal effects of PjBL.